The Effect of ISBT-Bowen Therapy in the Treatment of Myofascial Neck Pain—a Randomized, Single-Blinded Clinical Trial - Ying, Chee L.A.; Lee, Tsz M.A.; Chen, Pik Yu; Samy, Winnie; Au, Lap Y.F.; Siu, Chi H.D. (International Journal of Therapeutic Massage & Bodywork, 2023)
Background: Myofascial pain syndrome (MPS) is the most common diagnosis in patient presenting with chronic nonspecific neck pain. It affects people’s work performance, productivity, and quality of life. To date, there is little research evaluating the effectiveness of non-invasive techniques, such as ISBT-Bowen Therapy in managing neck MPS. Objectives: To investigate the effectiveness of Bowen therapy in managing myofascial pain syndrome with symptoms lasting for more than six weeks. The study will also examine the long-term effect of ISBT-Bowen Therapy on functional enhancement, quality of life, and physical and mental well-being. Methods: This is a prospective, single-blinded randomized controlled trial (RCT). A total of 90 myofascial neck pain patients were recruited and randomized to receive 8 sessions of ISBT-Bowen Therapy over a 12-week period (n = 45) or to continue their usual conventional treatment (n = 45). Pressure pain threshold (PPT), cervical range of motion (CROM), numerical rating pain scores, Neck Disability Index (NDI), SF-12 Health Survey (SF-12) Version 2, Generalized Anxiety Disorder 7-item (GAD7), and Patient Health Questionnaire (PHQ9) were measured at baseline, 12 weeks, and 24 weeks after baseline. Results: When compared with the control group, PPT significantly increased after ISBT-Bowen Therapy at 12 and 24 weeks. CROM on flexion, lateral flexion, and rotation were greatly improved at 12 weeks after Bowen therapy, and maintained at 24 weeks, except left lateral flexion. NDI, GAD7, and PHQ9 were all reduced after Bowen Therapy at both 12 and 24 weeks. Both Physical and Mental Component Summary scores of SF-12 were improved after Bowen therapy at 12 and 24 weeks. Conclusions: This study confirmed the efficacy of ISBT-Bowen Therapy for patients with MPS. It alleviates pain, improves functional outcomes, enhances quality of life, and relieves mood symptoms.